Hydranencephaly: Insights into Pathophysiology and Management - Sedain, Gopal; Rajbhandari, Binod (Nepal Journal of Neuroscience, 2020)
Hydranencephaly is a rare and severe form of congenital disorder in which there is absence of cerebral cortex which is replaced by fluid. The presentation is in the form of hydrocephalus and developmental delay. There are various reports on possible etiopathogenesis and management. However, the overall prognosis is grim and clinicians especially in low and middle-income countries like Nepal often face a clinical judgement dilemma regarding management options to offer to the patient family. The ethical issue whether to offer cerebrospinal fluid diversion or not is always there. This review is aimed at discussing the various aspects of management of this pediatric neurosurgical problem.